The Influence of Financial Technology (Fintech), Financial Literacy, and Income on Financial Inclusion of Society - Chikmah, Isnani Farichatul; Karsono, Lorena Dara Putri (Labkat Press KA FTIK UNIKOM, 2024)
This study seeks to determine if financial technology (fintech), Financial Literacy, and income impact financial inclusion in society. This research was conducted quantitatively involving Generation Z from the former Pati Residency. Generation Z are those born in 1995-2010. Financial literacy can be used as a measuring tool to determine the extent to which a person understands financial concepts, ability to manage, and confidence in making long-term planning decisions by taking into account economic conditions. Likewise, income can serve as an indicator of an individual's financial management capabilities. The research results show that Fintech and Income partially have a significant effect on Financial Inclusion with statistical tests on the Fintech variable obtaining a t-count significance value of 0.000 the Income variable, with a value of 0.008, is less than 0.05, and the regression coefficients are positive, being 0.516 and 0.204 respectively. Financial Literacy does not have a significant effect on Financial Inclusion because based on testing the significance value of the calculated t is 0.095, where this figure is greater than 0.05. However, all three simultaneously influence society's financial inclusion. This was concluded from statistical testing of the coefficient of determination and the F test which obtained a value of 0.686. Increasing Community Financial Inclusivity can improve the economy evenly.